Nephrotic syndrome in children- Role of intravenous cyclophosphamide in comparison with oral cyclophosphamide in frequently relapsing or steroid dependent cases (Journal of Dhaka National Medical College & Hospital, 2014)
Introduction: Nephrotic syndrome in children is a disease of relapse and remission. The treatment of frequently relapsing (FR) and steroid dependent (SD) idiopathic nephritic syndrome(INS) with oral cyclophosphamide creates problem like side effects, infections and compliance.Methods: A prospective study was conducted among 27 patients selected consecutively selected, of them 19 were FR and 8 were SD idiopathic nephritic syndrome. Fourteen children were treated with Intravenous Cyclophosphamide (IVCP) at a dose of 500mg/m2/month for 6 months after achieving a steroid induced remission. Thirteen children were treated with Oral Cyclophosphamide(OCP) 2mg/kg/day for 12 weeks in case of SD and 3mg/kg/day for 8 weeks in case of FR nephritic syndrome. The response of IVCP & OCP were evaluated in terms of remission, change in steroid response status of the patient, duration of remission(ie. proteinuria free days), side effects & compliance with therapy.Results: The mean proteinuria free days (243.5 # 108.9 days in IVCP group vs 136.3# 73.3 days in OCP group) which was highly significant (p=0.004). The cumulative remission in the IVCP group 71.4% at one year follow up and was comparable to that of OCP group which was 46.2% at a 40% lower cumulative dose.Conclusion: Monthly intravenous cyclophosphamide pulse therapy causes prolonged remission with negligible side effect in frequently relapsing and steroid dependent idiopathic nephritic syndrome in childrenJ. Dhaka National Med. Coll. Hos. 2014;20(01):15-20